The Values of Islamic Character Education in the Film ‘My Name is Khan’ - Imam Bahroni; Izzatul Muna (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
Besides being part of the process of forming the morality or moral nation, character education is also expected to be the main foundation in improving Indonesian nation. However, it will not happen without a total planting of characters from various fields. One aspect that cannot be denied and kept out of the public at large is the fact of entertainment world, which including the television shows and films. One of the films considered bringing some positive values and strong character is the film My Name Is Khan. The purpose of this study was to examine the values of Islamic educational character in the film My Name Is Khan. This study used qualitative methods in the form of library research, which is the major information resource is media, such as books, magazines, internet, etc. The analysis used the analysis Semiotics of Roland Barthes. Semiotics is a method of research that examines the signs of an object, and Roland Barthes refined it so that semiotics can also be used to observe and examine the social action or called myth. From this research, it was discovered the values of character education Siddiq, Tabligh, Amanah and Fathonah from the dialogues, scenes, settings, as well as the gesturess of the actors. Those values are taken and packaged in the form of events in the film. Those values are implemented with a lot of adjustments, so that the film can be enjoyed and accepted by the entire community.